Planning Road Construction Based On Smart City: Challenges And Solutions - Teras, Deni; Tjahjono, Budi; Ridwan, Ridwan; Saepudin, Aep; Arniansyah, Arniansyah; Leihitu, Donny Dwy Judianto; Zebua, Dermawan (Innovative Research in Civil and Environmental Engineering, 2024)
This study investigates the challenges and solutions associated with the planning and implementation of smart city-based road construction in developing countries. Utilizing a descriptive qualitative approach, the research incorporates semi-structured interviews with key stakeholders, including government officials, technology developers, and urban planners. Findings indicate that budgetary constraints, a lack of technical expertise, and outdated regulatory frameworks significantly hinder the adoption of smart technologies in road infrastructure projects. Furthermore, the study highlights the potential of public-private partnerships and data-driven decision-making as viable solutions to these challenges. The results emphasize the necessity for collaborative models and innovative funding strategies to promote the effective integration of smart technologies in road planning and construction, ultimately enhancing urban infrastructure sustainability.